Effects of lidocaine-plus-meloxicam treatment on behavioral and physiological changes, and leukocyte heat shock protein 90 gene expression after surgical castration in Hanwoo bulls - Cho, Ingu; Yoo, Seonpil; Jung, Da Jin Sol; Lee, Jaesung; Baek, Seok-Hyeon; Kim, Sang Yeob; Lee, Jinoh; Kim, Dohyun; Kim, Hyun Jin; Baik, Myunggi (Frontiers in Veterinary Science, 2024)
This study examined the effects of surgical castration and lidocaine-plus-meloxicam treatment on growth, physiology, behaviors, and leukocyte heat shock protein 90 (HSP 90) gene expression in Hanwoo (Korean cattle) bulls. Twenty Hanwoo bulls (body weight 248.8 ± 28.5 kg, age 9.4 ± 1.04 months) were assigned to three treatments: surgical castration with lidocaine injection (5 mL in the scrotum) and oral meloxicam administration (1 mg/kg body weight; LM; n = 7); surgical castration with placebo injection (5 mL of 0.9% NaCl) and oral placebo administration (lactose, 1 mg/kg body weight; CAS; n = 7); and shame castration (SHAM; n = 6). Meloxicam and lactose were administered 3 h before castration, and lidocaine and NaCl were injected immediately before castration. Surgical castration was performed with a Newberry knife and a Henderson castration tool. Wight was measured the day before and 14 d after castration, and behavior was observed from 0.5 h to 4.5 h post-castration. Blood was collected at −1 d, 0.5 h, 6 h, 1 d, 3 d, 7 d, and 14 d after castration to measure plasma cortisol, haptoglobin, and leukocyte HSP 90 mRNA. Castration tended to decrease average daily gain (p = 0.06), but the LM treatment did not affect weight gain. Bulls in CAS showed higher cortisol concentration (p < 0.05) at 0.5 and 6 h after castration compared to SHAM, with no difference between CAS and LM. Castration increased haptoglobin concentration at 1 and 3 d after castration (p < 0.05) while LM bulls showed decreased haptoglobin concentration (p < 0.05) than CAS bulls at these times. HSP90 mRNA was increased at 6 h post-castration while LM did not reduce its expression, suggesting HSP90 may serve as an acute stress marker in castrated bulls. Castration increased (p < 0.05) frequencies of drinking, lying, walking, leg lifting, kicking, and stiff gait, while decreasing (p < 0.05) eating frequency. LM alleviated (p < 0.05) drinking, leg lifting, kicking, and stiff gait. Collectively, castration resulted in physiological changes, increased leukocyte HSP90 gene expression, and altered behaviors. These findings suggest that lidocaine-plus-meloxicam treatment partially mitigates pain and inflammation in the castrated bulls.